KAJIAN KARAKTERISTIK FISIK, MEKANIK DAN AERODINAMIK DAUN TEH HASIL PETIKAN YANG TELAH DILAYUKAN - Agus Sutejo; Mardjan Suro Sutrisno; Hermawan Wawan; Desrial Desrial (The University of Lampung, 2020)
The design of the wilted tea stalk and leaf separation system aims to improve the quality of the tea produced especially by separating the tea leaves and stalks at the beginning of the process. Stages that are needed to be done include designing a chopper machine that is capable of chopping tea stems and leaves to a certain size and designing stem and leaf separation system with the pneumatic principle with suction. In this study, physical, mechanical and aerodynamic characteristics of tea leaves were measured. The result showed that force to release a leaf is in the range of values between 12.24-16.17 N smaller than the need for the cutting force of the stem and leaves and the greatest difference in force is achieved at a water content between 55 and 58% bb (leaves) and 66-68% bb (stalk). The leaf terminal velocity is <3 m s-1 while the tea terminal velocity is > 9 m s-1. Tea leaf yield value is very important as a reference in testing the performance of tea and tea leaf separator machines where the average leaf yield is 77.33% and the average stem yield is 22.67%. Keywords: characteristic of tea leaves, engineering, separation of tea leaves, withering of tea leaves